Pengaruh Pembelajaran Project Based Learning (PjBL) pada Materi Ekosistem terhadap Sikap dan Hasil Belajar Siswa SMAN 2 Malang - Susriyati Mahanal; Ericka Darmawan; A. D. Corebima; Siti Zubaidah (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The objective of this research was to know the effect of Project Based Learning (PjBL) to the attitude and student cognitive achievement in SMAN 2 Malang. This research applied quasy experimental with non-equivalent control group design. The populations of this research is all student of class X SMAN 2 Malang on academic year 2008/2009. The samples of this research were class X7 as experimental (PjBL) and class X8 as control (conventional). The instrument of this research namely cognitive achievement test and attitude scale questionnaire to river ecosystem. This research data are quantitative data consisted by score cognitive achievement and attitude scale questionnaire to river ecosystem, collected on 14 Maret until 31 May 2009. Data were analysed by bilinear covariant statistical analysis (Ancova), continued with LSD test. The result of this research indicated that there were PjBL toward the cognitive achievement and student attitude to river ecosystem. Students with PjBl having attitude higher 11,65% from conventional students. Beside, students with PjBl having cognitive achievement higher 81,05% from conventional students. Based on this research, the researcher suggest to the teacher that this strategy can be implemented in biology learning. Kata kunci: Project Based Learning, sikap terhadap ekosistem sungai, hasil belajar